مكانة اللغة العربية في دعم تنمية المجتمع: دراسة أدبية حول الدوافع والأساليب في عصر 5.0 - Ana Achoita (Yayasan Mutiara Hati Moeslem, 2025)
The Arabic language is a common bond among people in the Maghreb and the Mashreq, and a great link between a number of nations. Its connection is one of the strongest ties, and colloquial language alone is insufficient to unite these peoples, even though it is now spoken everywhere and has different dialects, because each people has its own unique way of speaking it. The Arabic language greatly influences other languages, and one manifestation of this influence is that many of the world's languages use the Arabic script for writing. It is also the key to knowledge, the lamp of understanding, and the means of perceiving what a person finds and what falls under their eyes and ears. It enables its owner to send rays of his thoughts to his people, so that they may perceive the light of his insights and find no obstacles of dogma in their path that would prevent the seekers from achieving his goal.